A quantitative and qualitative assessment of sugar beet genotype resistance to root-knot nematode, Meloidogyne incognita - Gohar, Ibrahim M. A.; Alyamani, Amal; Shafi, Manal E.; Mohamed, Elshaimaa A. E.; Ghareeb, Rehab Y.; Desoky, Elsayed M.; Hasan, Mohamed E.; Zaitoun, Amera F.; Abdelsalam, Nader R.; El-Tarabily, Khaled A.; Elnahal, Ahmed S. M. (Frontiers in Plant Science, 2023)
Two outdoors pots experiments were performed in 2018 and 2019, to evaluate host suitability of sugar beet genotypes for root-knot nematode, Meloidogyne incognita according to adapted quantitative scheme for assignment of Canto-Saenz’s host suitability (resistance) designations (AQSCS). The degree of susceptibility or tolerance of the examined genotypes was recorded by the modified host-parasite index (MHPI) scale, which takes into account the degree of loss in technical characteristics and production induced by nematode infection. In addition, single nucleotide polymorphism (SNPs) was detected. Eight varieties of sugarbeet were evaluated against M. incognita. Sugarbeet varieties have been classified into four categories for their susceptibility or tolerance according to the MHPI scale. The first category (MR) implies only one variety named SVH 2015, which did not provide for nematode reproduction (RF ≤1), and root damage by them was minimal (GI ≈2). Second, the tolerant group (T) involving Lilly and Halawa KWS which supported fairly high nematode reproduction (RF >1) with relatively plant damage (GI≤2). Whereas susceptible (S) category involved in 4 varieties, FARIDA, Lammia KWS, Polat, and Capella, which supported nematode reproduction factor (RF >1) with high plant damage (GI >2). The fourth category refer to the highly susceptible (HS) varieties such as Natura KWS that showed (RF≤1) and very high plant damage (GI>2). Results exhibited that there were significant differences among these categories towards root damage (gall index), final population, reproduction factor (R-factor), and susceptibility rate. R-factor, as well as the quality and yield traits, were evidently reduced by M. incognita to a considerable level. The MHPI scale could be ranked as standardization of host suitability method sugarbeet to root-knot nematodes. Whereas AQSCS technique is suitable for quick sugarbeet plants host suitability test, especially for the susceptible sugarbeet varieties. The alignment and amino acid composition prediction of the DNA sequences revealed the presence of five SNPs among all sugar beet verities. Therefore, this study introduce a rapid and effective screening procedure to detect numbers of sugarbeet genotypes with resistance to root-knot nematodes through modified conventional susceptibility assessments. Besided, utilizing the SNPs to determining the susceptibility or tolerance degree of varieties.